ANALISIS YURIDIS AKIBAT PERKAWINAN PASANGAN PRIA DENGAN WANITA YANG TIDAK SESUAI DENGAN PASAL 2 UNDANG-UNDANG NOMOR 1 TAHUN 1974 - DEALITA NIM. A1011191217 (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstracThings that often happen in society in carrying out marriages are not in accordance with the provisions of Article 2 paragraph (2) of Law Number 1 of 1974, namely marriages that are legal if each marriage is registered under the provisions of the applicable laws and regulations, marriages that are only carried out legally according to Islamic religious law but not recorded according to state law, still legal according to Islamic religious law but marriages that are not carried out at the KUA (Office of Religious Affairs) for those who believe in Islam and for those who are of a religion other than Islam in KCS (Office of Civil Registry) are basically will have an impact on not having permanent legal force, in this case the parties who are most harmed are the wife and children, the wife cannot file a lawsuit because in order to file a lawsuit she must have a marriage certificate as authentic evidence and children who do not have a civil relationship with the father . The implementation of unregistered marriages can occur due to a lack of public understanding of the law, as well as quite expensive costs, then it is synchronized in making the implementation of these regulations, namely referring to Article 2 paragraph (1) and paragraph (2), this creates differences of opinion, so there are still some people who carry out marriages that are not in accordance with Law Number 1 of 1974.The title in this study is Juridical Analysis of the Consequences of Marriages for Couples of Men and Women That Are Not In Accordance with Article 2 of Law Number 1 of 1974, the formulation of the problem